Dependence of female ball in handball repulsion on the pressure within this sport - Bjelica, D.; Popovic, S.; Tanase, G. D.; Gardasevic, J. (Acta Kinesiologica, 2017)
The aim of this research is to determine the elastic (repulsive) properties of female ball in handball depending on the air pressure in it. Female ball in Handball of standard dimensions was released on the flat solid surface from the height of nine meters for four times. At the first release the air in the ball was under prescribed pressure. At the second release the pressure in the pumped ball is reduced by 5%, at the third reduced by an additional 5%, at the fourth reduced by another 5%. The setting of the experiment was carried by cinema shooting of free fall of the prescribed handball and a series of rebounds after the rejection of solid surfaces. One can conclude that the distance crossed and the total duration of four successive bouncing mostly dependent on inner pressure. In this study, the initial speed of a female ball in handball was unchanged and only inner pressures were changed. It was determined how much the height of the rebound is reduced and the duration of the rebound, respectively, depending on the reduction of inner pressure. Overall, it can be concluded that the initial speed of the ball can be increased by increasing the inner pressure in the ball.